The link between interest rates on interbank money and for credit lines: are asymmetric interest rate adjustments empirically evident? - Petra Korndörfer (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1997)
The paper investigates the behaviour of banks with regard to the pricing of commercial short term loans over the period from 1975 until 1997. Due to the inclusion of interest rate quotes by banks located in east Germany in 1991 we distinguished between the subperiods from 1975 – 1989 and 1991 – 1997. In the context of the price setting for credit lines we focus on the commonly held belief of asymmetric interest rate adjustments. In order to raise the markup on credit lines banks adjust rates on credit lines slower when refinance rates are decreasing. Estimating error correction models a longterm relation between the rate for interbank money and for credit lines is established. In order to test for asymmetric interest rate adjustments non-symmetric error correction models as well as error correction models with asymmetric short-term dynamics are estimated. The hypothesis of asymmetric interest rate adjustments is confirmed largely by the estimation results of the latter specification while in the former specification no asymmetry is found. – – In diesem Beitrag wird das Preissetzungsverhalten von Banken bezüglich kurzfristiger Unternehmenskredite untersucht. Der Untersuchungszeitraum beginnt 1975 und endet 1997. Aufgrund der Berücksichtigung von Banken aus den neuen Bundesländern ab 1991 werden zwei Teilperioden (1975 – 1989 und 1991 – 1997) unterschieden. Kernpunkt der Untersuchung ist die Überprüfung der weitverbreiteten Annahme asymmetrischer Zinsanpassungen. Die Asymmetriehypothese beruht auf der Annahme, daß Banken um ihre Zinsmargen zu erhöhen, während Zinssenkungsphasen die Kreditzinsen langsamer an Veränderungen der Refinanzierungssätze anpassen als sonst. Durch das Schätzen von Fehlerkorrekturmodellen werden langfristige Beziehungen zwischen Geldmarkt- und Kontokorrentzinsen hergestellt. Um die Annahme asymmetrischer Zinsanpassungen zu untersuchen werden nicht-symmetrische Fehlerkorrekturmodelle und Fehlerkorrekturmodelle mit Asymmetrie in der kurzfristigen Dynamik geschätzt. Die Ergebnisse letzterer Schätzung stützen im allgemeinen die Asymmetriehypothese, während in der ersten Spezifikation keine Asymmetrie nachweisbar ist.
Keywords: 330